2020
DOI: 10.3390/ijerph17249295
|View full text |Cite
|
Sign up to set email alerts
|

What are the Critical Elements of Satisfaction and Experience in Labor and Childbirth—A Cross-Sectional Study

Abstract: The labor experience and satisfaction with childbirth are affected by the care provided (external factors) and individual variables (internal factors). In this paper, we present a descriptive analysis that aims to indicate the strongest correlates of birth experience among a wide range of indicators. The study is a prospective, cross-sectional, self-report survey. It includes the experiences of women giving birth in public and private hospitals in Poland. The two main variables were birth experience and satisf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…“Offering the woman and her family the information they need in a clear and concise manner” is one of the recommendations regarding effective communication between maternity care providers and women in labour [ 29 ]. Feeling informed (about birth process, personnel roles, child’s health during birth and about how to feed the child) significantly affects birth experience [ 30 ]. In our study, verbal communication was more often assessed as helpful in the maternity ward than during labour and birth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…“Offering the woman and her family the information they need in a clear and concise manner” is one of the recommendations regarding effective communication between maternity care providers and women in labour [ 29 ]. Feeling informed (about birth process, personnel roles, child’s health during birth and about how to feed the child) significantly affects birth experience [ 30 ]. In our study, verbal communication was more often assessed as helpful in the maternity ward than during labour and birth.…”
Section: Discussionmentioning
confidence: 99%
“…It may result from the fact that the woman in early postpartum is focused on receiving messages and information about the baby, so she may prefer the verbal communication, focusing on the newborn, as well as touching and holding him/her. Breastfeeding support and information are also important aspects at this point, affecting both overall birth experience [ 30 ] as well as breastfeeding duration [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…It may result from the fact, that the woman in puerperium is focused on receiving messages and information about the baby, so she may prefer the verbal communication, focusing on the newborn, as well as touching and holding him/her. Breastfeeding support and information are also important aspects at this point, affecting both overall birth experience [30] as well as breastfeeding duration [31].…”
Section: Discussionmentioning
confidence: 99%
“…A study has shown that the delivery environment was the main factor contributing to satisfaction with labor [18]. Martins et al likewise reported that a non-abusive and respectful environment was one of the factors affecting women's satisfaction with childbirth.…”
Section: Introductionmentioning
confidence: 99%